Modal Manusia, Modal Struktural dan Modal Pelanggan Dalam Meningkatkan Kinerja Keuangan UMKM - Kadek Dwi Purnami; I Putu Julianto (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This research aims to determine the influence of human capital, structural capital and customer capital on the financial performance of MSME. This type of research is quantitative research. The population in this study is all MSME actors recorded in the profile of MSMEs in the Department of Trade, Industry and Cooperatives, Small and Medium Enterprises Buleleng Regency, which is as many as 131 people. This research sample is determined by saturated sampling technique (census) which means that the entire research population is sampled. The data was collected using questionnaires with the scale used i.e. likert scale. Then the data is analyzed with several analyses, namely data quality tests that include validity tests and reliability tests, classic assumption tests that include normality tests, multicolinearity tests and heterokedastisity tests as well as multiple linear regression analyses assisted by spss 23 programs. The results showed that human capital has a positive and significant influence on financial performance, structural capital has a positive and significant influence on financial performance, and customer capital has a positive and significant influence on financial performance. Keywords : human capital, structural capital, customer capital, financial performance